Sergius, the Paulician Leader, in the Account by Peter of Sicily - Wolińska, Teresa (Studia Ceranea, 2019)
Peter of Sicily, a Byzantine high official from the times of Basil I, intended to warn the Archbishop of Bulgaria against certain heretics, known as the Paulicians, as he learned during his mission to Tefrike about their plans of sending their missionaries there. His writings are regarded as the most competent source of information on the history and doctrine of the Paulicians. He also described some of their leaders, including Sergius himself. According to Peter, it was a woman with whom Sergius had had an affair who made him the devil’s tool. He accepted the name of Tychicos and passed himself off as a disciple of Paul the Apostle. For 34 years he was the leader of the Paulicians. Peter admits that Sergius was successful in winning followers and at the same time, besides making false statements, accuses him of selling Christians into slavery to barbarians and of collaboration with the Muslims. In the end, however, he was supposed to have an argument with another heresiarch, Baanes, which would lead to a break among the Paulicians. Sergius is colourfully described as an enemy of the Cross, a voice of impiety, a lover of darkness and a wolf in sheep’s clothing, who skilfully pretends to be a man of virtue but has deceived many. Although he himself was murdered in 834/835, his work was continued by disciples of his.